Work-Life Balance, Work Engagement, And In-Role Performance: Moderating Roles Of Self-Efficacy - Jufrizen Jufrizen; Dedek Kurniawan; Lucy Ela Febrianti (International Journal Reglement & Society (IJRS), 2023)
The research aims to analyze several aspects, including the influence of work-life balance on in-role performance, the influence of work-life balance on work engagement, the influence of work engagement on in-role performance, the influence of work-life balance on in-role performance mediated by work engagement, and the influence of work-life balance on work engagement moderated by self-efficacy. This study adopts an associative research design with a sample of 40 respondents who are employees at PT. Jasa Marga (Persero) Tbk Belmera Medan Branch. Data collection techniques involve statement lists such as questionnaires, and data analysis utilizes Path Analysis. The Partial Least Square (SmartPLS) application tests the five hypotheses proposed in this study. The research findings indicate that the influence of work-life balance on in-role performance is positive and significant, the influence of work-life balance on work engagement is positive and significant, the influence of work engagement on in-role performance is positive and significant, the influence of work-life balance on in-role performance mediated by work engagement is positive and significant (implying that work engagement mediates the influence of work-life balance on role performance). The influence of work-life balance on work engagement moderated by self-efficacy is positive and significant (indicating that self-efficacy moderates the influence of work-life balance on work engagement).